DInSAR Analysis and Analytical Modeling of Mount Etna Displacements: The December 2018 Volcano‐Tectonic Crisis. Issue 11 (7th June 2019) - De Novellis, V.; Atzori, S.; De Luca, C.; Manzo, M.; Valerio, E.; Bonano, M.; Cardaci, C.; Castaldo, R.; Di Bucci, D.; Manunta, M.; Onorato, G.; Pepe, S.; et al.
Abstract: We investigate the 24–27 December 2018 eruption of Mount Etna occurred from fissures located on the volcano eastern flank and accompanied by a seismic swarm, which was triggered by the magma intrusion and continued for weeks after the end of the eruption. Moreover, this swarm involved some of the shallow volcano‐tectonic structures located on the Mount Etna flanks and culminated on 26 December with the strongest event (ML 4.8), occurred along the Fiandaca Fault. In this work, we analyze seismological data and Sentinel‐1 Differential Interferometric Synthetic Aperture Radar (DInSAR) measurements, the latter inverted through analytical modeling. Our results suggest that a dike source intruded, promoting the opening of the eruptive fissures fed by a shallower dike. Moreover, our findings indicate that the activation of faults in different sectors of the volcano may be considered as a response to accommodate the deformations induced by the magma volumes injection. Key Points: We investigate the ground displacements and the 3D source geometry of the December 2018 Mount Etna (Italy) volcano‐tectonic crisis DInSAR data obtained from SAR data pairs collected by Sentinel‐1 have been inverted through analytical modeling Our results suggest the presence of two volcanic sources: a shallow dike and a deeper one associated with a long‐term seismic swarm